2021
DOI: 10.1371/journal.pone.0251761
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, treatment, and survival in small cell lung cancer in Spain: Data from the Thoracic Tumor Registry

Abstract: Background Small-cell lung cancer (SCLC) is an aggressive disease with high metastatic potential and poor prognosis. Due to its low prevalence, epidemiological and clinical information of SCLC patients retrieved from lung cancer registries is scarce. Patients and methods This was an observational multicenter study that enrolled patients with lung cancer and thoracic tumors, recruited from August 2016 to January 2020 at 50 Spanish hospitals. Demographic and clinical data, treatment patterns and survival of SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Some reported prognostic factors include performance status (PS), increased age, male gender, and numerous metastatic sites at baseline [ 4 ]. But certainly, prognosis is largely related to the stage of the disease and therapeutic approach: whereas LS disease is potentially curable, with 20–30% of patients alive at 5 years and median overall survival (mOS) ranging between 25 and 30 months [ 5 ], while patients with ES disease have poor mOS of 10–13 months and 5-year survival rates of < 5% [ 1 , 6 , 7 ]. Smoking is known to be the primary risk factor for SCLC [ 6 ], and therefore, smoking prevention or cessation are key strategies to diminish the clinical impact of the disease.…”
Section: Incidence and Epidemiologymentioning
confidence: 99%
“…Some reported prognostic factors include performance status (PS), increased age, male gender, and numerous metastatic sites at baseline [ 4 ]. But certainly, prognosis is largely related to the stage of the disease and therapeutic approach: whereas LS disease is potentially curable, with 20–30% of patients alive at 5 years and median overall survival (mOS) ranging between 25 and 30 months [ 5 ], while patients with ES disease have poor mOS of 10–13 months and 5-year survival rates of < 5% [ 1 , 6 , 7 ]. Smoking is known to be the primary risk factor for SCLC [ 6 ], and therefore, smoking prevention or cessation are key strategies to diminish the clinical impact of the disease.…”
Section: Incidence and Epidemiologymentioning
confidence: 99%
“…Only 10.9% of cases developed brain metastasis, which is similar to the biological behavior of P-SCLC. 18,19 Furthermore, multivariate analysis revealed that brain metastasis and liver metastasis were correlated with unfavorable OS in C-SCLC. Therefore, consistent with P-SCLC, liver metastasis [20][21][22] and brain metastasis 23 are also crucial negative prognostic factors of OS for patients with C-SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the International Association for the Study of Lung Cancer 1 show that the 2-year overall survival rate of the SCLC group of stages I, II, III, and IV is about 73%, 54%, 23%, and 8%, respectively. Data from Spain 2 indicate that 96.7% of SCLC patients could be present with metastases, with approximately 20% having brain metastases at the time of diagnosis. The overall survival was about 9.5 months, with the 1-year and 2-year survival rates being 38.9% and 14.8%, respectively.…”
Section: Introductionmentioning
confidence: 99%